A phase I/II trial of olaparib tablet in combination with eribulin in Japanese patients with advanced or metastatic triple-negative breast cancer previously treated with anthracyclines and taxanes. (March 2019) - Yonemori, Kan; Shimomura, Akihiko; Yasojima, Hiroyuki; Masuda, Norikazu; Aogi, Kenjiro; Takahashi, Masato; Naito, Yoichi; Shimizu, Satoru; Nakamura, Rikiya; Hashimoto, Jun; Yamamoto, Harukaze; Hirakawa, Akihiro; et al.
Abstract: Background: We conducted a multicenter phase I/II trial of olaparib plus eribulin in Japanese patients with advanced or metastatic triple-negative breast cancer (TNBC) to determine the recommended phase II dose (RP2D) (phase I) and to examine the efficacy and safety (phase II) (UMIN00009498) of the combined therapy. Patients and methods: In phase I, olaparib tablet was orally administered twice daily from level 1:25 mg BID to level 7:300 mg BID, with 1.4 mg/m 2 of eribulin on days 1 and 8. In phase II, patients were treated with RP2D to assess the response rate (independent review). The planned sample size was 24 with a threshold of 10%. Results: One of the 24 patients enrolled in phase I experienced dose-limiting toxicity. The RP2D was established as 300 mg twice daily for olaparib and 1.4 mg/m 2 for eribulin. Among the 24 patients in phase II, the median number of administered courses was 5.5 (range: 1–28). Grade ≥III adverse events included neutropenia (83.3%), leucopenia (83.3%), anaemia (41.7%), febrile neutropenia (33.3%) and thrombosis (8.3%). The response rate was 29.2% (independent; N = 7/24; 90% confidence interval [CI]; 14.6–47.9). Median progression-free survival and overall survival were 4.2 (95% CI, 3.0–7.4) and 14.5 (95% CI, 4.8–22.0) months, respectively. Germline BRCA1/2 mutation status was observed in three patients in phase I and 2 patients in phase II, respectively. The Cmax and area under the curve for olaparib increased in a dose-dependent manner, and these parameters for eribulin and olaparib were not influenced by each other. Conclusions: Combination therapy of olaparib with eribulin shows antitumour activity against advanced or metastatic TNBC, but caution must be exercised in the presence of febrile neutropenia. Highlights: Olaparib combined with eribulin showed efficacy in patients previously treated with anthracycline and taxanes. In pharmacokinetics, no drug interaction between eribulin and olaparib was observed. Poly(ADP-ribose) polymerase inhibition was observed from the lowest dose of olaparib.